Health Status Evaluation of Limestone Mine Workers - Dhatrak, Sarang Vilas; Nandi, Subroto Shambhu; Chatterjee, Debasis Mrinal; Dhumne, Umesh Laxman (National Journal of Community Medicine, 2014)
Introduction: Mining is a hazardous occupation in which workers are exposed to adverse conditions. In India, limestone mining is carried out in a large scale and there are 549 reported mines producing about 154 million tonnes. Objective: The present study was carried out in a limestone mine in India to determine the morbidity pattern among workers engaged actively in mining activities. Methodology: 152 workers engaged actively in mining activities were included. The health status of the employees was evaluated by well defined medical questionnaire along with pulmonary function test (PFT). Results: Findings of the study showed poor literacy rate amongst the miners. Lung function test showed restrictive impairment in about 15% of miners. Hypertension, diabetes and musculoskeletal morbidity were prevalent in miners. Conclusion: The study findings indicate the need for regular health checkups, health education, personal protective devices and engineering control for better health and productivity of the miners.